Analysis on restoring stiffness and its hysteresis behavior of slender catenary mooring-line. (1st August 2020) - Li, Yilun; Guo, Shuangxi; Chen, Weimin; Yan, Dingbang; Song, Jixiang
Abstract: In deeper ocean area, more and more floating oil/gas production platforms or wind turbine have been in operation instead of the fixed truss in shallow water. These floaters need to be located among a range of position by its mooring system, e.g. tension tendon and catenary mooring-line, so as to guarantee structural safety and stability under environmental loads. Catenary mooring-line is increasingly used due to its lower cost and easier installation. Its dynamics coming from structure and fluid flow becomes more obvious with the increase of structural length, which may introduce significant impact on restoring performance of mooring-line. In this study, the non-linearly restoring performance and the hysteresis behavior of mooring-line's stiffness are studied. The nonlinear dynamic model of the mooring-line is established based on the improved FEM simulations. It is found that the restoring stiffness of the catenary mooring-line presents a hysteresis characteristic, principally owing to the damping effect of the catenary dynamics, which gets more obvious with the increase of motion amplitude/frequency. And, the mooring-line dynamics has significant impacts on the tension (related to its restoring stiffness) and displacement response, e.g. the maximum tension amplitude is up to 5.2 times of the quasi-static value if slack happens. Highlights: The non-linearly restoring performance of catenary mooring-line's stiffness is studied using our improved FEM model. It is found that the restoring stiffness presents a hysteresis, mainly owing to the damping effect of catenary dynamics. And the hysteresis becomes more obvious with the increase of top-end frequency ω d and amplitude A 0, i.e. approximately in a way of being proportional to ω d 2 A 0 3 . Impacts of mooring-line's hysteresis on catenary response are presented based on the numerical simulations. The maximum tension has a significant increase compared with the quasi-static one.